Place and Memory Excavations at the Pict's Knowe, Holywood and Holm Farm, Dumfries and Galloway, 1994-8 - Thomas, Julian (Oxbow Books, 2007)
This volume is concerned with the investigation of three complexes of prehistoric ceremonial monuments in the immediate environs of Dumfries in the south-west of Scotland, conducted between 1994 and 1998. These were the Pict's Knowe henge, the Holywood cursus complex, and the post alignments/cursus at Holm. The field research was designed in such a way as to recognise that prehistoric monuments often have complex and individual sequences of construction and use, while also acknowledging that detailed studies of particular sites and local contexts will ultimately advance our understanding of monumentality in prehistoric Europe. The three sites of the Pict's Knowe, Holywood and Holm have proved especially helpful in addressing questions of how particular places maintained their importance over long periods of time. In each instance the location was characterised by features which possess a high degree of archaeological visibility. In the former case it was the upstanding earthwork of the bank and ditch that identified the site as a henge monument, while Holywood and Holm were discovered through aerial photography. Each of the sites investigated had complex sequences of development, in which the structural elements that were recognised prior to fieldwork were not necessarily the most important or the most long-lived. This book considers the details of the excavated features, environmental and artefactual evidence, as well as more general concerns. The first part of the volume concentrates on the Pict's Knowe, while the second looks at the more spatially and typologically related sites of Holywood and Holm.